2020
DOI: 10.18488/journal.1.2020.102.142.150
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Validation of an Integrated Learning Method Based on Problem-Based Learning in a Pedagogy, Technology and Assessment Course at Malaysia Public Universities

Abstract: The study aims to develop and test a Problem-Based Learning (PBL) Learning Module the KPD3016-Teaching, Technology and Assessment course as one of the pedagogical strategies that will assist and become a benchmark for lecturers or educators in promoting and strengthening the abilities of students and graduates of the Bachelor of Education degree programmes in soft skills (such as thinking skills, self-learning, group work, communication skills, leadership, entrepreneur, etc). The module produced is current and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Moreover, this initiative facilitates the fulfillment of students' needs, offering diverse teaching methodologies and learning sessions that reignite their enthusiasm for the history subject. These enjoyable teaching techniques not only foster cognitive development but also act as motivational catalysts, stimulating students to delve deeper into historical topics (Chen, Wang, Chen, & Chen, 2014;Md. Zabit et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, this initiative facilitates the fulfillment of students' needs, offering diverse teaching methodologies and learning sessions that reignite their enthusiasm for the history subject. These enjoyable teaching techniques not only foster cognitive development but also act as motivational catalysts, stimulating students to delve deeper into historical topics (Chen, Wang, Chen, & Chen, 2014;Md. Zabit et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding the research on the integration mode of university science and technology innovation and urban emerging industry development, Sain K et al [28] found that after exploring the academic behaviors of university researchers by developing an integrated early warning system based on artificial intelligence, the interaction modes between universities and urban industries mainly include four categories of joint participation, mutual influence, joint action, and close relationship, due to the different starting points and interest-driven degrees of research behaviors Ali M [29] and Mariani D [30] suggested that through the integration of demand analysis and local cultural wisdom, it is possible to scientifically differentiate talent teams, establish a differentiated talent evaluation system, innovate a "comprehensive + dynamic" training model for scientific and innovative talents, and establish a talent pool for urban development. Zabit M N [31] took the development and validation of the integrated learning method of problem learning as an example of the science and technology evaluation system of "basic research for the world and applied research for the market", revised the relevant policies and texts, innovated the interaction mode with evaluation as the main body, and promoted universities to actively adapt to the development of urban emerging industries. Son K S et al [32] proposed a triple interaction model of "R&D platformresearch team-technology innovation" based on the integration of university and city, taking into account the development characteristics of urban emerging industries and the impact of common cause failure and periodic testing.…”
Section: Introductionmentioning
confidence: 99%
“…The PBL learning model positively affects students' academic achievement and attitudes towards learning and developing students' concepts and misconceptions in the classroom, (Hairuddin et al, 2018). The PBL learning model is the key for students to transfer the knowledge and skills they learn in math class to real life and solve everyday problems, (Nazir Md. Zabit et al, 2020).…”
Section: Introductionmentioning
confidence: 99%